A study of crystalline â texture and anisotropic properties of hexagonal BaFe12O19 sintered by in-situ magnetic-anisotropy spark plasma sintering (MASPS) - Mohammed, H.G. (Elsevier B.V., 2022)
In-situ magnetic-anisotropy spark plasma sintering technique (MASPS) was used to produce an anisotropic pellet of BaFe12O19 at different sintering parameters. The crystalline texture and anisotropic properties were studied and investigated by using XRD, FESEM, EDX, relative magnetic texture, and mechanical anisotropy. Among all sintered samples, S1180 exhibited (00L) preferred orientation with a high degree of texture (Lotgering factor and texture coefficient TC are 0.78 and 7.17 respectively), which has resulted from XRD patterns. FESEM images confirmed that the grains were grown and re-oriented along the magnetic easy axis. From the EDX test, the degrees of crystalline texture were 59.18, 5.26, and â5.54 of S1180, S1050, and S920, respectively. S1180 had the highest mechanical anisotropy, where the hardness on the top surface and the cross-section are 603 and 60.8 HV, respectively. Besides, the highly textured sample (S1180) had the highest relative density (88.76) and the lowest porosity (11.23). Moreover, the relative degree of magnetic texture (D) of S1180 was 73.97. Â© 2022 Elsevier B.V.